Shape memory polymer foams prepared from a heparin-inspired polyurethane/urea. Issue 34 (8th March 2017) - Chai, Q.; Huang, Y.; Kirley, T. L.; Ayres, N.
Abstract : Shape memory foams have been prepared using a heparin-inspired polyurea/urethane that displays excellent resistance to platelet adherence. Abstract : Polymers with shape memory properties have been prepared using heparin-inspired segments. The polymers have been prepared as films and foams. Both films and foams demonstrate good shape memory behavior as evidenced by fixity and recovery values. The materials properties of the foams can easily be tuned by varying the template used to prepare the foam. The heparin-inspired polymers impart excellent resistance to platelet adhesion. These shape memory foams are promising candidates for blood contacting biomaterials.